2017
DOI: 10.18632/oncotarget.23025
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ analysis of a mouse acute myocardial infarction model reveals that vitamin D binding protein promotes cardiomyocyte apoptosis after hypoxia

Abstract: The proteome profile changes after acute myocardial infarction (AMI) and the roles played by important protein species remain poorly understood. Here, we constructed a mouse AMI model by ligating the left coronary artery of male C57B/6J mice to investigate the molecular changes after AMI on the protein level. Total proteins of the left ventricle were extracted and quantitatively analyzed by isobaric tags using relative and absolute quantitation (iTRAQ) technologies. The transcript and protein levels of importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Nonetheless, in serum samples of patients with ST-elevation myocardial infarction (STEMI) the proteomic approach identified increased levels of DBP when compared to control donors, confirmed by the Western blot analysis [ 36 ]. These findings were confirmed by those recently published on the proteome profile changes after acute myocardial infarction (AMI) in an experimental model, where the expression levels of DBP and vitamin D receptor (VDR) were found increased in both left ventricular tissue of AMI mouse model, suggesting that DBP might be involved in left ventricular remodeling, and H9C2 cells, promoting cardiomyocyte apoptosis, after hypoxia [ 37 ].…”
Section: Vitamin D and Biomarkers Of Bone Turnoversupporting
confidence: 73%
“…Nonetheless, in serum samples of patients with ST-elevation myocardial infarction (STEMI) the proteomic approach identified increased levels of DBP when compared to control donors, confirmed by the Western blot analysis [ 36 ]. These findings were confirmed by those recently published on the proteome profile changes after acute myocardial infarction (AMI) in an experimental model, where the expression levels of DBP and vitamin D receptor (VDR) were found increased in both left ventricular tissue of AMI mouse model, suggesting that DBP might be involved in left ventricular remodeling, and H9C2 cells, promoting cardiomyocyte apoptosis, after hypoxia [ 37 ].…”
Section: Vitamin D and Biomarkers Of Bone Turnoversupporting
confidence: 73%
“…Integrated proteomic-metabolomics is a powerful combination [8] and provides a better understanding of dynamic molecular change. Some studies have reported the changes of metabolites and proteins in plasma or myocardium after MI [9][10][11]; however, the integrated proteomic-metabolomics in myocardium after an MI has not been reported. Thus, we designed an integrated proteomic-metabolomics study, to comprehensively understand the pathological changes and the mechanisms of MI.…”
Section: Introductionmentioning
confidence: 99%
“…According to the GO analysis, the BP term 'translation' mainly affected protein synthesis, which otherwise resulted in the production of dysfunctional proteins. 'Translation' has been previously reported correlated to AMI [25]. Donko et al also stated that the unique genes in degenerative heart disease encoded proteins in the 80 S ribosome complex (term 'translation') [26].…”
Section: Discussionmentioning
confidence: 96%